The politics of tourism representations: Discourse analysis of British travel brochures about incredible India - BIPITHALAL BALAKRISHNAN NAIR (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research examines how India has been portrayed in UK travel brochures. This research aims to analyze travel brochure portals in terms of both their content and their overall context.Methodology: A qualitative approach informed by an interpretive paradigm was used for this study. The researchers used a systematic sampling strategy to collect the information. Techniques from the field of discourse analysis were used to examine the data.Findings: This research offers a glimpse into how British tourism literature portrays India for potential visitors. This analysis sheds light on why the projections based on the country’s current geopolitical power and economic growth don’t add to the full picture.Novelty/Implications: Even though India is now widely acknowledged as a major global power, this study also supports the stereotype of India as a backward, orientalism-laden, colonial relic.